Occurrence of the Trissolcus basalis, egg parasite of Nezara viridula, in Brazil - Ferreira, Beatriz S. Corrêa (Pesquisa Agropecuaria Brasileira, 2014)
A description is given of the occurrence of the microhymenopterous T. basalis, a little black wasp, parasiting eggs of N. viridula which is considered one of the most important insect pests attacking soybean crops. Althoug the parasitism levels have had low effects, the use of this species would become an auxiliary practice in controlling that bug by reducing the damages and the production costs.